PENGARUH MEDIA EDUCAPLAY TERHADAP PEMAHAMAN SISWA MATERI KERJA SAMA DI LINGKUNGANKU KELAS IV SD NEGERI 48 PANGKALPINANG: Penelitian Skripsi - Anggun Permatasari; Diana Pramesti; Eka Wahyuningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Several issues motivate this research, including students' difficulties in grasping educational content, students' poor scores on the topic of cooperation in my environment, and the use of less interactive learning media when presenting the topic. The aim of this research is to measure the impact of Educaplay media on students' understanding of the Cooperation in my Environment material in class IV of SD Negeri 48 Pangkalpinang. This study adopts a quantitative approach using the quasi-experimental experimental design method of a non-equivalent control group type. This research is based on a complete sampling technique, involving two distinct classes: the experimental class (IVA) which uses the educational media Educaplay, and the control class (IVB) which uses conventional learning. Data collection methods include observation, documentation, and writing question reviews. Data analysis techniques use normality tests (Kolmogorov-Smirnov), homogeneity tests (Levene), and hypothesis testing using the independent samples t-test. According to the results of the normality test (Kolmogorov Smirnov), the pretest and posttest values in the experimental class were obtained as follows: (0.200 and 0.200) while those in the control were (0.200 and 0.083). All data followed a normal distribution, as the significant value was greater than 0.05. The results of the homogeneity test (Levene's) indicated a t-value of 3.833, above the critical value of 2.002, with a significance level of 0.001, which is less than 0.05. Therefore, it is concluded that the alternative hypothesis (Ha) is accepted. This means that there is an influence of Educaplay media on the understanding of the material of Cooperation in My Environment among the students of class IV of SD School Negeri 48 Pangkalpinang. The use of Educaplay media has a positive effect on student understanding, observable through changes in student behavior during the learning process. Students who previously lacked attention and had difficulty grasping educational content became more dynamic, passionate and focused when participating in learning.